Segmented Work, Divided Workers: The Historical Transformation of Labor in the United States - Frisch, Michael H. (Labour / Le Travail, 1984)
This article reviews the book, "Segmented Work, Divided Workers: The Historical Transformation of Labor in the United States", by David M. Gordon, Richard Edwards, and Michael Reich.